Konfirmation i en neoliberal tidsalder - Jacobsen, Brian Arly (Politik, 2014)
The neoliberal discourse is part of a larger shift from democratic to neoliberal policies that has been occurring over the past several decades; a shift accompanied by both discursive and structural changes in society. If the neoliberal discourse is transforming the core functions of government around the world, then this must also be true in the case of the close co-operation between the Danish state and the national church in Denmark. In this paper the cases of con ict over and transformation of the position of con rmation teaching in Den- mark is analyzed in order to nd out if the changes is a result of neoliberal policies in Denmark or simply a matter of structural changes caused by another rational basis. e friction over con rmation teaching is not only about the position of con rmation teaching in or out of school but a case showing consequences of how the neoliberal discourse is transforming religious authority in Danish society.